2019
DOI: 10.1038/s41467-019-12528-4
|View full text |Cite
|
Sign up to set email alerts
|

Engineering selective competitors for the discrimination of highly conserved protein-protein interaction modules

Abstract: Designing highly specific modulators of protein-protein interactions (PPIs) is especially challenging in the context of multiple paralogs and conserved interaction surfaces. In this case, direct generation of selective and competitive inhibitors is hindered by high similarity within the evolutionary-related protein interfaces. We report here a strategy that uses a semi-rational approach to separate the modulator design into two functional parts. We first achieve specificity toward a region outside of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 80 publications
(102 reference statements)
2
50
0
Order By: Relevance
“…Using a phage display selection approach with a 10 FN3derived library, we have recently isolated and characterized three monobodies targeting PSD-95 (Rimbault et al, 2019). The clones were targeted against PSD-95 tandem PDZ domains and showed remarkable specificity for PSD-95, in particular when considering the high sequence conservation of paralogs (SAP97, SAP102 and PSD-93).…”
Section: Introductionmentioning
confidence: 99%
“…Using a phage display selection approach with a 10 FN3derived library, we have recently isolated and characterized three monobodies targeting PSD-95 (Rimbault et al, 2019). The clones were targeted against PSD-95 tandem PDZ domains and showed remarkable specificity for PSD-95, in particular when considering the high sequence conservation of paralogs (SAP97, SAP102 and PSD-93).…”
Section: Introductionmentioning
confidence: 99%
“…To verify γ2 S44* accumulation along the Z-projected dendritic shaft (Fig. 4d), we co-expressed γ2 S44* with the PSD-95 marker XPH20 fused with eGFP (XPH20::eGFP) 48 as a reporter and found that γ2 S44* accumulation was indeed always colocalized with the XPH20 eGFP signal (Fig. 4k).…”
Section: Resultsmentioning
confidence: 97%
“…The plasmid for the expression of the tRNA/aminoacyl transferase pair (pNEU-hMbPylRS- 4xU6M15, herein termed PylRS/4xtRNA Pyl ) was a gift from Irene Coin (Addgene, #105830) 44 . The plasmid for the expression of the Xph20 eGFP CCR5TC (XPH20::eGFP) was a gift from Matthieu Sainlos 48 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50] Ligand discovery for PDZ domains has proven challenging (e.g. fragment-based screening was unsuccessful for the PDZ domain of PSD-95 51 ), with the majority of potent ligands based on protein 52,53 , peptide 54,55 or peptidomimetic scaffolds 26,[56][57][58] and limited examples of small-molecules. [59][60][61][62] This rendered the GKAP/SHANK-PDZ interaction as a stringent test for our dynamic ligation screening approach.…”
Section: Introductionmentioning
confidence: 99%